Plant Prebiotics and Their Role in the Amelioration of Diseases - Kaur, Amrit Pal; Bhardwaj, Sonali; Dhanjal, Daljeet Singh; Nepovimova, Eugenie; Cruz-Martins, Natália; Kuča, Kamil; Chopra, Chirag; Singh, Reena; Kumar, Harsh; Șen, Fatih; Kumar, Vinod; Verma, Rachna; et al. (Biomolecules, 2021)
Prebiotics are either natural or synthetic non-digestible (non-)carbohydrate substances that boost the proliferation of gut microbes. Undigested fructooligosaccharides in the large intestine are utilised by the beneficial microorganisms for the synthesis of short-chain fatty acids for their own growth. Although various food products are now recognized as having prebiotic properties, several others, such as almonds, artichoke, barley, chia seeds, chicory, dandelion greens, flaxseeds, garlic, and oats, are being explored and used as functional foods. Considering the benefits of these prebiotics in mineral absorption, metabolite production, gut microbiota modulation, and in various diseases such as diabetes, allergy, metabolic disorders, and necrotising enterocolitis, increasing attention has been focused on their applications in both food and pharmaceutical industries, although some of these food products are actually used as food supplements. This review aims to highlight the potential and need of these prebiotics in the diet and also discusses data related to the distinct types, sources, modes of action, and health benefits.
Keywords: nemoc; zdraví; rostliny; střevní mikroflóra; dietary fiber; potravní vláknina; Gastrointestinal Microbiome; oligosaccharides; Plants; Prebiotics; prebiotika; prebiotics; Disease; zvířata; Humans; Dietary Fiber; short-chain fatty acids; Health; non-digestible carbohydrates; lidé; Animals